Avaliação do uso do teste de micronúcleo em células esfoliadas como biomarcador para o desenvolvimento do câncer oral em usuários de bebidas alcoólicas e anti-sépticos bucais - Rocha, Rodrigo dos Santos (2011)
Chromosomal damage (Micronucleus) and apoptosis (sum of Karyorrexis, Condensed chromatin and Picnosis) were analyzed in users of mouthwashes and/or alcoholic beverages using the Micronucleus Tests in exfoliated cells from oral mucosa according Tolbert et al. (1992) protocol, aiming evaluate both the genotoxic effects of these habits and the use of this test as biomarker of cancer risk. Sample analyzed included four groups of individuals, three exposed groups (GE) and a control group (GC), each one formed by twenty individuals. Exposed group 1 (GE1) was formed by users of mouthwashes; GE2 by drinkers and GE3 by users of both. Smears were done with cells collected by gentile scraping of cheek and were fixed in methanol/acetic acid (3:1) solution and stained and counterstained, respectively, with Schiff and Fast green. Endpoints were computed in two thousand cells in a blind fashion. Statistical analysis showed that chromosomal damage and apoptosis were significantly higher in individual of GE1 and GE3 as compared with GC (p<0,005 and p< 0,001, respectively). Was not observed significant difference in chromosomal damage and apoptosis as compared just exposed groups. Apoptosis occurrence, but not chromosomal damage was significantly higher in individuals of GE2 when compared with GC. These results suggest that mouthwashes alone or in association with alcohol beverage ingestion induce genotoxic effects manifested as chromosomal damage and apoptosis. Alcoholic beverages are effective in stimulate the apoptotic process. More studies are necessary to establishing useful of the Micronucleus Test as biomarker of cancer risk, but the results here described are enough to avoid indiscriminate use of mouthwashes and alcoholic beverages.